THE EFFECT OF E-SERVICE QUALITY AND WAITING TIME TOWARDS CUSTOMER SATISFACTION AT PIZZA HUT RESTAURANT IN MANADO TOWN SQUARE - Angle Livia Natalia Kapojos; David P. E. Saerang; Emilia M. Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
According to YouGov’s assessment, three US-based Quick Service Restaurant (QSR) brands the best in Indonesia YouGov placed Kentucky Fried Chicken (KFC) at the top as the brand with the best fast food title in 2021 in Indonesia. The brand bagged 37.3 points. Its rival, McDonald's came in second with 30.6 points. Pizza Hut followed with 28.6 points. The purpose of this study was to determine the effect of E-Service Quality, and Waiting time on Customer Satisfaction at Pizza Hut Restaurant in Manado Town Square. The research method used in this study is quantitative. The data analysis techniques used in this research is multiple linear regression analysis, using the IBM SPSS 26 statistical program. The results of this study state that E-service Quality (X), and Waiting Time (X2) have a positive and significant effect on Customer Satisfaction (Y), and then simultaneously Customer satisfaction and Waiting Time have a significant effect on Customer Satisfaction.   Keyword: e-service quality, waiting time, customer satisfaction